Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (ODI/GLAM, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.